2022
DOI: 10.3389/fpls.2022.827166
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Can Mediate Local Adaptation and Response to Climate Change in the Clonal Plant Fragaria vesca: Evidence From a European-Scale Reciprocal Transplant Experiment

Abstract: The ongoing climate crisis represents a growing threat for plants and other organisms. However, how and if plants will be able to adapt to future environmental conditions is still debated. One of the most powerful mechanisms allowing plants to tackle the changing climate is phenotypic plasticity, which can be regulated by epigenetic mechanisms. Environmentally induced epigenetic variation mediating phenotypic plasticity might be heritable across (a)sexual generations, thus potentially enabling rapid adaptation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 70 publications
(96 reference statements)
2
29
0
2
Order By: Relevance
“…We suggest that the assumption is reasonable as it is generally accepted that the 5-azaC reduces DNA global methylation through the effect on DNA methyltransferases, an enzyme that bonds methyl group on DNA 128 , 129 . We have also provided an evidence in our previous studies that the foliar application of 5-azaC reduces overall DNA methylation level by 4–30% in treated Trifolium repens, Taraxacum brevicorniculatum and Fragaria vesca plants 42 , 54 , 130 . In a grass, Oryza sativa , foliar application of 75 µM 5-azaC solution reduced their overall DNA methylation level by more than 50% 131 .…”
Section: Discussionsupporting
confidence: 60%
“…We suggest that the assumption is reasonable as it is generally accepted that the 5-azaC reduces DNA global methylation through the effect on DNA methyltransferases, an enzyme that bonds methyl group on DNA 128 , 129 . We have also provided an evidence in our previous studies that the foliar application of 5-azaC reduces overall DNA methylation level by 4–30% in treated Trifolium repens, Taraxacum brevicorniculatum and Fragaria vesca plants 42 , 54 , 130 . In a grass, Oryza sativa , foliar application of 75 µM 5-azaC solution reduced their overall DNA methylation level by more than 50% 131 .…”
Section: Discussionsupporting
confidence: 60%
“…In rice, it was show that a high affinity potassium transporter gene is regulated by DNA methylation in its promoter in order to maintain potassium and sodium homeostasis during salinity stress [ 15 ]. A notable example concerning environmental impacts on DNA methylation is the documented loss of methylation at TEs at high altitudes and how it may contribute to local adaptation in natural populations of wild strawberry [ 16 , 17 ]. However, whether stress-induced methylome alterations at individual loci or across the entire genome contribute to heritable changes in DNA methylation patterns and adaptation remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…One additional cause of phenotypic variation is epigenetic variation (Cubas et al ., 1999; Manning et al ., 2006; Xie et al ., 2015). Several studies have shown that epigenetic variation can be spatially structured among and within plant populations, and that such a structure can be associated with environmental variation and phenotypic differentiation (Lira-Medeiros et al, 2010; Medrano et al, 2014; Avramidou et al, 2015; Kawakatsu et al, 2016; de Kort et al, 2020; Boquete et al, 2021; Galanti et al, 2022, Sammarco et al, 2022). Although causal relationships remain to be studied, such observations suggest that epigenetic variation could contribute to the acclimation of plants to changes in environmental conditions.…”
Section: Introductionmentioning
confidence: 99%